THE DEVELOPMENT OF INTERCULTURAL COMMUNICATION SKILLS AMONG STUDENTS OF NON-LINGUISTIC HIGHER EDUCATION INSTITUTIONS IN UZBEKISTAN - Tokhta Ametovna Yuldasheva (Western European Studies, 2025)
This article explores the development of intercultural communication skills among students of non-linguistic higher education institutions in Uzbekistan. It highlights the significance of fostering effective communication abilities in an increasingly globalized academic and professional environment. The research focuses on identifying barriers to intercultural dialogue and offers strategies for overcoming these challenges through educational practices. By integrating theoretical insights and practical examples, this study emphasizes the importance of intercultural competence as a key skill for future educators in pedagogical programs.
Keywords: intercultural communication; non-linguistic universities; educational practices